2023
DOI: 10.1155/2023/1292762
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Oxidation of Organic Dye by Fe2O3 Nanoparticles: Catalyst, Electron Acceptor, and Polyurethane Membrane (PU-Fe2O3) Effects

Abstract: The textile industry’s discharges have long been regarded as severe water pollution. The photocatalytic degradation of dyes using semiconductors is one of the crucial methods. The present study efficiently used the mechanical method to synthesize Iron oxide Nanoparticles. XRD, FT-IR, UV-Vis DRS, and Raman analyses were performed to analyze the structural and optical. From the data provided by XRD and Raman data, we believed that the as-synthesized Iron oxide was pure hematite (α-Fe2O3) with a hexagonal structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…As is quite pertinent from previous literature reports, synthetic iron oxides have a point of zero charge (PZC) value lying between 7 and 9. 49 The surface of the catalyst becomes positively charged, favouring electrostatic interactions with the anionic dyes, as soon as the pH value drops below pHpzc. As per the findings of the study involving the degradation of Eosin Yellow dye in the presence of the synthesized catalyst conducted at different pH values of 2, 4, 6, 8, 10 and 12, it was observed that the best results were obtained at pH 6, showing a degradation efficiency of more than 15% than that at pH 12 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As is quite pertinent from previous literature reports, synthetic iron oxides have a point of zero charge (PZC) value lying between 7 and 9. 49 The surface of the catalyst becomes positively charged, favouring electrostatic interactions with the anionic dyes, as soon as the pH value drops below pHpzc. As per the findings of the study involving the degradation of Eosin Yellow dye in the presence of the synthesized catalyst conducted at different pH values of 2, 4, 6, 8, 10 and 12, it was observed that the best results were obtained at pH 6, showing a degradation efficiency of more than 15% than that at pH 12 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These NPs act as adsorbents for the successful removal of dyes. In their study, Balrabe et al [165] reported that eosin yellowish displayed efficient removal (95%) at 75 ppm using Fe 2 O 3 nanoparticles, pH 6, with a 15 min exposure time. In another study, Darwesh et al [168] reported the F. oxysporum OSF18 strain-synthesized CuO-NPs immobilized in alginate beads, which exhibited 90% dye remediation efficiency.…”
Section: Nanoparticles Based Bioremediationmentioning
confidence: 99%
“…Traditional methods of dye remediation are less effective and more expensive. In recent years, nano-bioremediation has emerged as a viable alternative for the effective and environmentally friendly removal of dyes from the environment [165]. Numerous industries, including agriculture, energy, medicine, and the environment, all use nanotechnology [14,166,167].…”
Section: Nanoparticles Based Bioremediationmentioning
confidence: 99%
“…A variety of catalysts have been employed for the degradation of organic dyes, such as Cu/Ni-doped nanostructures, Fe 2 O 3 nanoparticles, polymeric hydrogel containing TiO 2 nanoparticles, Fe 2 O 3 /ZnO, Fe 2 O 3 /SiO 2 , CeO 2 /Ce 2 S 3 composites, Ch-Pani/Fe 2 O 3 , C 3 N 4 /Fe 2 O 3 , polyaniline/SnO 2 nanospheres, Fe 2 O 3 /ZnTe, Fe 2 O 3 /Mn 3 O 4 , CuO/ZnO nanocomposites, and tellurium-based metal alloys [6,[11][12][13][14][15][16][17][18][19]. Among these catalysts, hematite (Fe 2 O 3 ) stands out for its remarkable qualities, which include resistance to corrosion, high efficiency, and non-toxicity [20].…”
Section: Introductionmentioning
confidence: 99%